Minimally Invasive Stent Screw–Assisted Internal Fixation Technique Corrects Kyphosis in Osteoporotic Vertebral Fractures with Severe Collapse: A Pilot “Vertebra Plana” Series - Cianfoni, A.; Delfanti, R.L.; Isalberti, M.; Scarone, P.; Koetsier, E.; Bonaldi, G.; Hirsch, J.A.; Pileggi, M. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Fractures with “vertebra plana” morphology are characterized by severe vertebral body collapse and segmental kyphosis; there is no established treatment standard for these fractures. Vertebroplasty and balloon kyphoplasty might represent an undertreatment, but surgical stabilization is challenging in an often elderly osteoporotic population. This study assessed the feasibility, clinical outcome, and radiologic outcome of the stent screw–assisted internal fixation technique using a percutaneous implant of vertebral body stents and cement-augmented pedicle screws in patients with non-neoplastic vertebra plana fractures.MATERIALS AND METHODS: Thirty-seven consecutive patients with vertebra plana fractures were treated with the stent screw–assisted internal fixation technique. Vertebral body height, local and vertebral kyphotic angles, outcome scales (numeric rating scale and the Patient’s Global Impression of Change), and complications were assessed. Imaging and clinical follow-up were obtained at 1 and 6 months postprocedure.RESULTS: Median vertebral body height restoration was 7 mm (+74%), 9 mm (+150%), and 3 mm (+17%) at the anterior wall, middle body, and posterior wall, respectively. Median local and vertebral kyphotic angles correction was 8° and 10° and was maintained through the 6-month follow-up. The median numeric rating scale score improved from 8/10 preprocedure to 3/10 at 1 and 6 months (P < .001). No procedural complications occurred.CONCLUSIONS: The stent screw–assisted internal fixation technique was effective in obtaining height restoration, kyphosis correction, and pain relief in patients with severe vertebral collapse.antanteriorBKPballoon kyphoplastyIQRinterquartile rangeLKAlocal kyphotic anglemidmiddleNRSnumeric rating scalePGICPatient’s Global Impression of ChangepostposteriorSAIFstent screw–assisted internal fixationVBvertebral bodyVBHvertebral body heightVKAvertebral kyphotic angleVPvertebra planaVBSVertebral Body Stenting SystemVCFvertebral compression fracture